Criancices e socialidade de base (Polifonia, 2002)
ABSTRACT: In this text we evoke the nursery rhymes and street games that brought the children together in the everyday life of Cuiabá 40 yeas ago. Apart from rebuilding and registering them with the help of the memory, especially of the women of Cuiabá that used to sing and play during that time, we also discussed the role of playing games in the engendering of the sociability. We also point out the factor that, by changing the scenery of the city of Cuiabá and the state of Mato Grosso, are responsible for the silencing and almost extinction of the oral culture.